Discovery of novel sulfonated small molecules that inhibit vascular tube formation - Raman, Karthik (2012)
Tumor-associated angiogenesis is a complex process that involves the interplay among several molecular players such as cell-surface heparan sulfate proteoglycans, vascular endothelial growth factors and their cognate receptors. PI-88, a highly sulfonated oligosaccharide, has been shown to have potent anti-angiogenic activity and is currently in clinical trials. However, one of the major drawbacks of large oligosaccharides such as PI-88 is that their synthesis often requires numerous complex synthetic steps. In this study, several novel polysulfonated small molecule carbohydrate mimetics, which can easily be synthesized in fewer steps, are identified as promising inhibitors of angiogenesis in an in vitro tube formation assay.